Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Chapter 1 - 1.6 - Other Types of Equations - 1.6 Exercises - Page 128: 49



Work Step by Step

$3x(x-1)^\frac{1}{2}+2(x-1)^\frac{3}{2}=0$ $\sqrt {x-1}(3x+2(x-1)) = \sqrt {x-1}(5x-2)=0$ x=1 or 2/5 Checking the solutions in the original equation x=2/5 is extraneous. (as x-1 should be >=0 for $\sqrt{x-1}$ to be defined)
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.